Batu Sebagai Simbol Pribadi Dalam Karya Seni Lukis - Rizky, Muhammad (Institut Seni Indoensia Surakarta, 2012)
Stone is represent object owning interesting characteristic, exotic, and have multifariously of symbol which not yet to exploration, specially will become symbol having the character of personal. Combination between experience of person among social reality, where stone as object at the same time to be subjectÂ which personate symbol of personality ( metaphor). Along with style combination of surrealistic and of minimalistic, created masterpiece make an impression on ' in' and is free.Keywords: stone, symbol, artistic of paint